Climate-smart agriculture appreciation event for the members of the Philippine Network of Environmental Journalists - Vidallo, Rene R.; Bayot, Ruvicyn S.; Anunciado, Ma. Sheila (2019)
The appreciation event was organized to provide the members of the media with the basic concepts about the effects of climate change to agriculture, and of the contribution of agriculture to climate change; to facilitate collection stories on field-based experiences through interactions with farmers who have adopted practices that helped them adapt to climate risks; and to showcase climate smart agriculture approaches in demo farms, school garden, and farmers field. Through this activity, they can also help IIRR extend its reach and scale-out learnings from various CSA initiatives. Once available, these media products will be collated.